2016
DOI: 10.1080/17538947.2016.1197328
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy–frequency ratio model for avalanche susceptibility mapping

Abstract: Avalanche activities in the Indian Himalaya cause the majority of fatalities and responsible for heavy damage to the property. Avalanche susceptibility maps assist decision-makers and planners to execute suitable measures to reduce the avalanche risk. In the present study, a probabilistic data-driven geospatial fuzzy-frequency ratio (fuzzy-FR) model is proposed and developed for avalanche susceptibility mapping, especially for the large undocumented region. The fuzzy-FR model for avalanche susceptibility mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Study area Method used in study Tien Bui et al (2012) Hoa Binh province, Vietnam Adaptive Neuro-Fuzzy Inference System Zare et al (2013) Vaz Watershed, Iran Multilayer perceptron and radial basic function Pham et al (2016) Uttarakhand state, India. Naïve Bayes Trees, Support Vector Machines Kumar et al (2016) Indian Himalayas Fuzzy-frequency ratio Pham et al (2017) Indian Himalayas Multiple Perceptron Neural Networks Kornejady et al (2017) Golestan Province, Iran Maximum Entropy Chen et al (2017a) Langao County, China. Rotation forest ensembles, Naive Bayes Tree Hong et al (2017) Chongren area, China Frequency ratio, Certainty factor, Index of entropy Nsengiyumva et al (2018) Eastern Province, Rwanda Spatially different criteria evaluation methods Polykretis et al (2019) Mediterranean catchment, Greece Adaptive neuro-fuzzy modeling Pham and Prakash (2019) MuCang Chai, northern Vietnam Bagging-based Naïve Bayes Trees Dou et al (2020aDou et al ( , 2020b Northern parts of Kyushu, Japan Support vector machine hybrid ensembles Wang et al (2020) Sichuan Province, China Deep belief network (DBN)…”
Section: Author Yearmentioning
confidence: 99%
See 2 more Smart Citations
“…Study area Method used in study Tien Bui et al (2012) Hoa Binh province, Vietnam Adaptive Neuro-Fuzzy Inference System Zare et al (2013) Vaz Watershed, Iran Multilayer perceptron and radial basic function Pham et al (2016) Uttarakhand state, India. Naïve Bayes Trees, Support Vector Machines Kumar et al (2016) Indian Himalayas Fuzzy-frequency ratio Pham et al (2017) Indian Himalayas Multiple Perceptron Neural Networks Kornejady et al (2017) Golestan Province, Iran Maximum Entropy Chen et al (2017a) Langao County, China. Rotation forest ensembles, Naive Bayes Tree Hong et al (2017) Chongren area, China Frequency ratio, Certainty factor, Index of entropy Nsengiyumva et al (2018) Eastern Province, Rwanda Spatially different criteria evaluation methods Polykretis et al (2019) Mediterranean catchment, Greece Adaptive neuro-fuzzy modeling Pham and Prakash (2019) MuCang Chai, northern Vietnam Bagging-based Naïve Bayes Trees Dou et al (2020aDou et al ( , 2020b Northern parts of Kyushu, Japan Support vector machine hybrid ensembles Wang et al (2020) Sichuan Province, China Deep belief network (DBN)…”
Section: Author Yearmentioning
confidence: 99%
“…As shown in Figure 2, nine factors were used in the study. The selected factors were the same as those used for analyzing the impact or sensitivity of landslides by other studies (Tien Bui et al 2012;Zare et al 2013;Kumar et al 2016;Pham et al 2016;Kornejady et al 2017;Nsengiyumva et al 2018;Polykretis et al 2019). Topographic (elevation, slope, aspect, curvature), geologic (lithology), environmental (road area ratio, forest area ratio), and meteorological (daily maximum precipitation) data pertaining to these variables were collected for analysis from National Geographic Information Institute, Korea Institute of Geoscience and Mineral Resources, Korean Meteorological Administration, and National Disaster Management Research Institute (Table 2).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, at an international level, an increasing trend exists in applying statistical modelling in the field of geosciences to a wide range of natural disasters, such as flooding (Cao et al, 2016), rock falls (Shirzadi et al, 2017), fires (Hong et al, 2017), avalanches (Kumar et al, 2016); others are applied for the assessment of human-induced modifications to the landscape (Al-sharif and Pradhan, 2016), cultural heritage (Nicu 2016a), water resources management (Mousavi et al, 2017), waste management (Taboada-Gonzáles et al, 2014), and renewable energy (Ahmad and Tahar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Early versions of GIS based avalanche terrain models (Ghinoi and Chung, 2005;Gruber and Haefner, 1995;Maggioni and Gruber, 2003) struggled to outperform simple slope based avalanche release area estimates (Voellmy, 1955) due to the inability of low resolution DEM (20-30 m) to detect small scale terrain features. Current PRA modelling methods evolved over the course of a decade and benefit from developments in high-resolution DEM production and remote sensing (Andres and Chueca Cía, 2012;Barbolini et al, 2011;Bühler et al, 2013Chueca Cía et al, 2014;Pistocchi and Notarnicola, 2013;Veitinger et al, 2016;Kumar et al, 2016Kumar et al, , 2019. Bühler et al (2013) found that 5 m DEM resolution is the optimal tradeoff between processing efficiency and small-scale feature identification for PRA modelling.…”
Section: Potential Avalanche Release Area Modellingmentioning
confidence: 99%